Mechanism Study on the Intrinsic Damage and Microchemical Interactions of Argillaceous Siltstone Under Different Water Temperatures - Ning Liang; Tao Jin; Jingjing Zhang; Damin Lu (Applied Sciences)
Argillaceous siltstone is prone to deformation and softening when exposed to water, which poses a great threat to practical engineering. There are significant differences in the degrees of damage to this type of rock caused by solutions with different water temperatures. This study aimed to better understand the effect of temperature on argillaceous siltstone by designing immersion tests at water temperatures of 5, 15, 25, and 35 °C, analyzing the mechanical properties and cation concentration shifts under each condition. A water temperature–force coupled geometric damage model for argillaceous siltstone was developed, incorporating a Weibull distribution function and composite damage factors to derive a statistical damage constitutive model. The findings reveal that, with increasing water temperature, the peak strength and elastic modulus of argillaceous siltstone display a concave trend, initially decreasing and then increasing, while the cation concentration follows a convex trend, first increasing and then decreasing. Between 15 and 25 °C, the stress–strain behavior transitions from a four-phase to a five-phase pattern, with pronounced plasticity. The model’s theoretical curves align closely with experimental data, with the Weibull parameters m and λ effectively capturing the rock’s strength and plastic characteristics. Changes in water temperature notably influence the damage variable D12 in the context of water temperature–peak stress coupling, with D12 initially increasing and then decreasing with higher temperatures. These research results can provide new methods for exploring the paths of soft rock disasters and provide guidance for designing defenses in geotechnical engineering.